Molecular characterization of orf virus from sheep and goats in Ethiopia, 2008–2013. Issue 1 (December 2016) - Gelaye, Esayas; Achenbach, Jenna; Jenberie, Shiferaw; Ayelet, Gelagay; Belay, Alebachew; Yami, Martha; Loitsch, Angelika; Grabherr, Reingard; Diallo, Adama; Lamien, Charles
Abstract Background Orf is a contagious disease of sheep, goats and wild ungulates caused by orf virus (ORFV) a member of the genus Parapoxvirus, Poxviridae family. Although orf is endemic in Ethiopia, little attention has been given so far as it is not a notifiable disease by the World Organization for Animal Health. In this work, we have investigated orf outbreaks representing five different geographical locations of Ethiopia, in Amba Giorgis, Gondar zuria, Adet, Debre zeit and Adami Tulu, between 2008 and 2013. Results The viral isolation and the sequence analysis of the A32L and the B2L genes of eighteen representative isolates confirmed that sampled animals were infected by ORFVs. The phylogenetic study and the comparative analysis of the deduced amino acid profile suggests that there were two main clusters of ORFV isolates which were responsible for the investigated outbreaks. Additionally the analysis of these two genes showed limited variability to ORFVs encountered elsewhere. This is the first report on the genetic characterization of the ORFV isolates from sheep and goats in Ethiopia. Conclusion The molecular characterization of Ethiopian ORFV isolates highlighted the circulation of two main clusters causing orf disease in sheep and goats. The use of laboratory based methods and a constant monitoring of Ethiopian ORFV isolates is needed to better understand the dynamic of ORFV circulating in the country and facilitate the implementation of control measures.